Scientific Formation Stages and Theoretical Foundations of Innovation Management in Education - Boltaeva, Sitora (The Lingua Spectrum, 2025)
This article explores the stages of scientific formation and the theoretical foundations underpinning innovation management within the educational sector. The primary focus is the diverse array of innovative processes implemented across various sectors of the national economy. These innovation processes constitute a complex, large-scale, and multifaceted object of management, necessitating specialized forms and methods of managerial influence to foster effective development and implementation. By integrating classical and contemporary management theories, the article underscores the critical role of scientific methods in organizing and directing innovation in education. It delves into how structured approaches can enhance the efficacy of innovation initiatives. The findings emphasize that robust innovation management is not merely a catalyst for national economic growth but also a vital prerequisite for the survival, commercial efficiency, and sustained competitiveness of enterprises in an increasingly globalized world. Effective innovation management ensures organizations remain adaptive and resilient, driving progress and fostering long-term success in dynamic economic landscapes.